ความสัมพันธ์ระหว่างความสามารถในการทำกำไรกับอัตราผลตอบแทนจาก ส่วนต่างราคาหุ้นของกลุ่มธุรกิจโรงพยาบาล และบริการด้านสุขภาพ ที่จดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - ศุภอักษร ชัญญาณิศา; ลิ่วคุณูปการ นิรันดิ์เกียรติ; กุฏิภักดี ฐานกุล; มั่นเศรษฐวิทย์ ศิษฏ์ธวัช (Al-HIKMAH Journal, 2019)
Abstract The objective of this study was to study the relationship between profitability and rate of return in capital gain yield of hospital business and health services listed in the Stock Exchange of Thailand. The research was conducted by analyzing the data collected from 14 companies and interview local investors. The results of this study were as follows: 1) The Profitability Ratio of Return on Asset (ROA) had positive relationship with rate of return in capital gain yield of Chiang Mai Ram Medical Business Public Company Limited at a significant level of 0.001. 2) The Profitability Ratio of Return on Equity (ROE) had positive relationship with rate of return in capital gain yield of Chiang Mai Ram Medical Business Public Company Limited at a significant level of 0.001. 3) The Profitability Ratio of Net Profit Margin (NPM) had positive relationship with rate of return in capital gain yield of Chiang Mai Ram Medical Business Public Company Limited at a significant level of 0.01. 4) The Profitability Ratio of Operating Income Margin (OIM) had positive relationship with rate of return in capital gain yield of Chiang Mai Ram Medical Business Public Company Limited at a significant level of 0.01. The results from the interviews with the local investors showed that the factors that may affect the spread shares of the hospital business group and health services include global and domestics economic, Thailand’s government policy in the development of International Health Center (MedicalHub), trends of health conscious and aging population, and the reputation and expansion of the company.